2022
DOI: 10.3389/fmed.2022.1054898
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression, and quality of life in children and adults with alopecia areata: A systematic review and meta-analysis

Abstract: IntroductionAlopecia areata (AA) is a non-scarring hair loss condition, subclassified into AA, alopecia universalis, and alopecia totalis. There are indications that people with AA experience adverse psychosocial outcomes, but previous studies have not included a thorough meta-analysis and did not compare people with AA to people with other dermatological diagnoses. Therefore, the aim of this systematic review and meta-analysis was to update and expand previous systematic reviews, as well as describing and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 111 publications
3
10
0
Order By: Relevance
“…Despite the fact that previous studies have suggested that women with vitiligo or AA experience lower QoL than men, 28,29 we did not find any gender‐related differences in QoL in either vitiligo or AA subjects. Notably, our finding is compatible with the results of van Dalen et al 23 . research on AA and Al‐Shammari et al 24 .…”
Section: Discussionsupporting
confidence: 94%
“…Despite the fact that previous studies have suggested that women with vitiligo or AA experience lower QoL than men, 28,29 we did not find any gender‐related differences in QoL in either vitiligo or AA subjects. Notably, our finding is compatible with the results of van Dalen et al 23 . research on AA and Al‐Shammari et al 24 .…”
Section: Discussionsupporting
confidence: 94%
“…Living with AA can also have deleterious consequences on psychosocial wellbeing, owing predominantly to its visible impact on appearance. 3 To manage the change in appearance, many use strategies to conceal or camouflage their hair loss. Wigs, for example, can reduce fear of negative evaluation from others and improve social confidence, 4 and can therefore be considered an orthotic for those choosing to use them.…”
Section: Introductionmentioning
confidence: 99%
“…Hair loss from AA typically begins with small patches on the scalp but can progress to its more severe forms involving total scalp (alopecia totalis) and body (alopecia universalis) hair loss. Living with AA can also have deleterious consequences on psychosocial wellbeing, owing predominantly to its visible impact on appearance 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an "it's just hair" perspective fails to consider the elevated levels of suffering and significant impact on quality of life (QOL) reported by many living with AA (Rencz et al, 2016). The existing research has shown that people with AA are at a significantly high risk of experiencing stigma (Schielein et al, 2020) and developing complex psychological problems, including self-esteem issues, anxiety, depression, and an increased risk of suicidality (e.g., Davey et al, 2019;Layegh et al, 2010;Hunt & McHale, 2005;van Dalen et al, 2022). For instance, Lee et al (2019) found that among people living with AA, 27.1% reported the presence of anxiety and 18.9% reported a diagnosis of depression.…”
mentioning
confidence: 99%